2019
DOI: 10.1177/2309499018825222
|View full text |Cite
|
Sign up to set email alerts
|

Grade 3 AC joint injury: A survey of current practice in the United Kingdom

Abstract: Acromio-clavicular (AC) joint injuries are a common injury seen in athletes and represent 9% to 12% of all shoulder injuries. There is no clear consensus on treatment of grade 3 injuries. We conducted a survey among upper limb surgeons in the United Kingdom to review commonly accepted practise. We found that majority of surgeons never did stress view. Most surgeons favoured surgery only if needed but not first choice. There is no consensus on timing of surgery. There are many fixation options available for AC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A systematic review examining type III injuries found equivalent clinical outcomes of patients managed operatively and nonoperatively, with a quicker return to work and sport for the nonoperative group [ 48 ]. Surveys have found that most surgeons manage type III injuries nonoperatively in the Netherlands [ 49 ], United Kingdom [ 50 ], and the United States [ 51 , 52 ].…”
Section: Management Of Acromioclavicular Joint Injuriesmentioning
confidence: 99%
“…A systematic review examining type III injuries found equivalent clinical outcomes of patients managed operatively and nonoperatively, with a quicker return to work and sport for the nonoperative group [ 48 ]. Surveys have found that most surgeons manage type III injuries nonoperatively in the Netherlands [ 49 ], United Kingdom [ 50 ], and the United States [ 51 , 52 ].…”
Section: Management Of Acromioclavicular Joint Injuriesmentioning
confidence: 99%
“…During the last decades numerous techniques to repair an acromioclavicular (AC) dislocation have been suggested [1][2][3][4][5][6]. Hereby the pendulum has swung from temporary transfixaton of the AC joint with K-wires or hook plates towards complex (extra-)anatomical soft tissue repair of the coracoclavicular (CC) ligaments [1,4,5]. These latest techniques demonstrated a restoration of the supero-inferior instability but did not provide adequate antero-posterior stability.…”
Section: Introductionmentioning
confidence: 99%
“…16 Decision-making for the treatment of type 3 AC joint injuries is the most highly controversial. 11 The International Society of Arthroscopy, Knee Surgery and Orthopaedic Sports Medicine (ISAKOS) Upper Extremity Committee subdivides type 3 injuries into subtypes 3A (stable) and 3B (unstable). 6 Its recommendation is that 3 weeks after an injury, a patient with a type 3 injury should undergo radiography in a special view, that is, the Alexander view 1 or the Basamania view, 4 to identify an unstable condition.…”
mentioning
confidence: 99%